Association between precocious puberty and obesity risk in children: a systematic review and meta-analysis - Song, Yongfu; Kong, Yibu; Xie, Xiaofei; Wang, Yongji; Wang, Na (Frontiers in Pediatrics, 2023)
The aim of this study was to evaluate the potential association between early onset puberty and the risk of different forms of obesity in children.The databases PubMed, EMBASE, Web of Science and Cochrane Library were systematically searched for relevant studies. The odds ratio (OR) and 95% confidence interval (CI) of obesity in precocious puberty were calculated using Stata software 14.0. A fixed-effects model was used if P > 0.1 and I 2 ≤ 50%. Otherwise, a random-effects model was used. Publication bias was assessed using funnel plots and Egger's test.The pooling analysis showed that precocious puberty in girls was associated with a higher risk of obesity (OR=1.98; 95%CI: 1.76-2.24; I 2 =0.00%, P<0.001). Girls with a history of precocious puberty were found to have an increased risk of general obesity (OR=2.03; 95%CI: 1.62-2.55; I 2 =22.2%, P<0.001), central obesity (OR=1.96; 95%CI: 1.70-2.26; I 2 =0.00%, P<0.001), and overweight (OR=2.03; 95%CI: 1.68-2.46; I 2 =5.1%, P<0.001). The pooled analysis showed that precocious puberty in boys was not associated with an increased risk of obesity (OR=1.14; 95%CI: 0.86-1.51; I 2 =50.6%, P=0.369). In boys, the occurrence of precocious puberty was not associated with an elevated risk of general obesity (OR=0.96; 95%CI: 0.40-2.27; I 2 =79.6%, P=0.922), central obesity (OR=1.17; 95%CI: 0.96-1.43; I 2 =0.00%, P=0.125), or overweight (OR= 1.03; 95%CI: 0.56-1.88; I 2 = 74.4%, P= 0.930).This meta-analysis suggests that the onset of puberty at an early age in girls is associated with an increased risk of obesity, however precocious puberty in boy was not associated with an increased risk of obesity. These findings highlight that precocious puberty should be considered an independent risk factor for obesity in girls.